Repeated gastroscopies at impendent relapse of bleeding from gastroduodenal ulcers - V. A. Stupin; S. V. Siluyanov; M. B. Sokhikyan; R. Yu. Tronin; R. Sh. Sardarov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate necessity and potentials of dynamic esophagogastroduodenoscopies (EGDS) at successful primary hemostasis in patients with high risk of relapse of bleeding.Material and methods. Retrospective analysis of case records of 332 patients hospitalized for bleeding from chronic stomach and duodenum ulcers was carried out. Evaluation of results in 122 patients after repeated EGDSs was carried out with account to causes of inefficiency of previous investigations.Results. Repeated gastroscopies were caused by: relapse of bleeding – in 21 (17,2%) patient, of them in 81% of cases it developed within first 3 days after primary examination, non-informative initial EGDS – in 12 (9,8%), control gastroscopy in dynamics – in 89 (73%). Frequently the bleeding relapses in early terms educed due to ineffective endoscopic hemostasis at active bleedings or absence of prophylaxis at high risk of relapse (Forrest IIA-IIB) at previous gastroscopy. Control gastroscopies in 55 (62%) patients were performed in 1 day after primary investigation that allowed in 6 patients with high risk of bleeding relapse to reveal active recurrent bleeding before its clinical manifestation. In 39 (32 %) patients further required repeated gastroscopies, 17 (14%) patients were urgently operated in relation to ineffective endoscopic hemostasis or high risk of bleeding relapse at repeated EGDSs. Of all patients 19 died (15,6%), of them 5 – in postoperative period.Conclusions. Principal causes of repeated gastroscopies were relapses of bleeding in early period after primary hemostasis and ineffective investigations. Relapses of ulcerative bleeding develop mostly in the first 3 days after primary hemostasis. At clinically significant relapses repeated gastroscopy with preventive actions is proven in patients with high operational risk on concomitant diseases (4–5 points by ASA scale). Repeated endoscopic investigations have no significant effect on clinical results of treatment of ulcerative bleedings, frequency of relapses, operative activity, mortality.